Crossing boundaries in rural research. (June 2022) - Eversole, Robyn
Rural places around the world share common issues related to their positioning outside social, political, and economic centres of power. More than simply tyranny of distance, many issues can be attributed to tyranny at distance: that is, the power of distant decision-makers to direct rural development from afar with little knowledge of rural contexts. In response to the challenge to progress a transformative research agenda for rural sociology, this article theorises a 'cross-boundary' approach to research for rural development, to address persisting issues of development ignorance. Cross-boundary knowledge production values the multiple, contextualised knowledges of rural people and brings these into dialogue with academic knowledges across disciplines to inform practical rural solutions. Rural sociologists, with their in-depth understanding of rural community dynamics and larger social structures, are ideally positioned to broker cross-boundary knowledge partnerships that equip rural communities to solve old problems in new ways.